Supplier Selection : A Study of the Supplier Selection Process within the Sporting Goods Manufacturing Industry - Smeja, Inken; Tenschert, Ulrike; Przewosnik, Dirk (Ekonomihögskolan, EHV, 2006)
Due to the ongoing globalisation and fast changes within the business environment companies are forced to adapt more quickly to customer needs. Therefore, they depend on reliable suppliers which provide them with the necessary goods and services. As a consequence, finding suitable suppliers is of utmost importance for companies. To be able to choose those suppliers companies need to establish criteria on which basis potential suppliers can be evaluate and select afterwards. Against this background, this master thesis researches the supplier selection process from the end manufacturer’s point of view. Hereby, the focus is laid on theoretical supplier evaluation criteria and methods. Due to the lack of investigations in this branch of industry the authors have chosen the sporting goods manufacturing industry within Sweden and Austria as their field of study. They have been supported in their research by the companies the Arctic City Counting House AB, the ATOMIC Austria GmbH, and the HEAD Sports AG which provided them with the essential empirical data. Keeping the above mentioned fact in the back of one’s mind, the authors deduce the following research question: On which basis and how do manufacturers of sports equipment in Sweden and Austria evaluate and select their suppliers? Within the theoretical part the reader of this thesis first of all gets an overview of supplier-buyer relationships and afterwards is informed about the structure of the supplier selection process, starting with the preparation step, followed by prequalification and evaluation steps and resulting in the final selection and the continuous controlling of the suppliers. In addition, common criteria which are necessary to evaluate suppliers are presented. Furthermore, the reader is provided with an insight into general evaluation models whereby four common theoretical methods are explained in detail (AHP, TCO, DCA, and DEA). Out of this theoretical data a conceptual model was created. The empirical part consists of practical information which ...